Principles of data wrangling : practical techniques for data preparation - Rattenbury, Tye; Hellerstein, Joseph M., 1968-; Heer, Jeffrey Michael; Kandel, Sean; Carreras, Connor (O'Reilly, 2017)
"A key task that any aspiring data-driven organization needs to learn is data wrangling, the process of converting raw data into something truly useful. This practical guide provides business analysts with an overview of various data wrangling techniques and tools, and puts the practice of data wrangling into context by asking, "What are you trying to do and why?""--Back cover.